Common variant of PDZ domain containing 1 (PDZK1) gene is associated with gout susceptibility: A replication study and meta-analysis in Japanese population. Issue 6 (December 2016) - Higashino, Toshihide; Matsuo, Hirotaka; Sakiyama, Masayuki; Nakayama, Akiyoshi; Nakamura, Takahiro; Takada, Tappei; Ogata, Hiraku; Kawamura, Yusuke; Kawaguchi, Makoto; Naito, Mariko; Kawai, Sayo; Takada, Yuzo; et al.
Abstract: PDZ domain containing 1 (PDZK1) is a scaffold protein that organizes a transportsome and regulates several transporters' functions including urate and drug transporters. Therefore, PDZK1 in renal proximal tubules may affect serum uric acid levels through PDZK1-binding renal urate transporters. Two previous studies in Japanese male population reported that a PDZK1 single nucleotide polymorphism (SNP), rs12129861, was not associated with gout. In the present study, we performed a further association analysis between gout and rs12129861 in a different large-scale Japanese male population and a meta-analysis with previous Japanese population studies. We genotyped rs12129861 in 1210 gout cases and 1224 controls of a Japanese male population by TaqMan assay. As a result, we showed that rs12129861 was significantly associated with gout susceptibility ( P = 0.016, odds ratio [OR] = 0.80, 95% confidence interval [CI] 0.67–0.96). The result of the meta-analysis among Japanese populations also showed a significant association ( P = 0.013, OR = 0.85, 95%CI 0.75–0.97). Our findings show the significant association between gout susceptibility and common variant of PDZK1 which reportedly regulates the functions of urate transporters in the urate transportsome.